2022
DOI: 10.3390/ijerph19052898
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Completeness of Foodborne Outbreak Reporting in the United States, 1998–2019

Abstract: Public health agencies routinely collect time-referenced records to describe and compare foodborne outbreak characteristics. Few studies provide comprehensive metadata to inform researchers of data limitations prior to conducting statistical modeling. We described the completeness of 103 variables for 22,792 outbreaks publicly reported by the United States Centers for Disease Control and Prevention’s (US CDC’s) electronic Foodborne Outbreak Reporting System (eFORS) and National Outbreak Reporting System (NORS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…By creating multi-pathogen and multi-location food preparation or consumption variables, we might have introduced potential multiplicity when comparing specific pathogen etiology, or location of preparation or consumption to their respective reference groups. Lastly, we paid sufficient attention to missing data and the structure of the missing data [50]. On the surface, we could handle missing data by using imputation; however, due to structural missingness, this could create bias.…”
Section: Discussionmentioning
confidence: 99%
“…By creating multi-pathogen and multi-location food preparation or consumption variables, we might have introduced potential multiplicity when comparing specific pathogen etiology, or location of preparation or consumption to their respective reference groups. Lastly, we paid sufficient attention to missing data and the structure of the missing data [50]. On the surface, we could handle missing data by using imputation; however, due to structural missingness, this could create bias.…”
Section: Discussionmentioning
confidence: 99%
“…9 Our analysis of completeness of foodborne outbreak surveillance system revealed that data quality could be improved with targeted efforts, well-defined criteria, and continuous assessments. 10…”
Section: Dire Consequences and Potential Solutionsmentioning
confidence: 99%
“…9 Our analysis of completeness of foodborne outbreak surveillance system revealed that data quality could be improved with targeted efforts, well-defined criteria, and continuous assessments. 10 Yet, data dashboards on their own are not sufficient. There needs to be greater collaboration with local experts and multidisciplinary teams to identify what might be missing from the data and why, how the missingness biases the results, how it can be avoided, and how the consequences of missingness can be communicated and addressed.…”
Section: Dire Consequences and Potential Solutionsmentioning
confidence: 99%
“…Surveillance of foodborne outbreaks plays a crucial role in the food industry due to the expanding scope of food distribution. The security and safety of distributed food hinges on the food producers’ capacity to recognize, detect, and track foodborne pathogens [ 1 ]. Pathogens transmitted through food and water can lead to a spectrum of infections, with outcomes spanning from mild fever to fatal consequences [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%